Ruang Publik yang Inklusif: Keamanan Psikologis dan Keselamatan Gender di Kawasan Pusat Kota - Bashiroh, Ainin; Bachriwindi, Aniqoh (Pusat riset dan Inovasi Nasional, 2024)
Fear of crime is closely linked to various factors such as education, income, race, age, and especially gender. Many studies have shown that women tend to experience higher levels of anxiety than men, thus limiting their participation in utilizing urban outdoor spaces. This condition emphasizes the need for crime prevention efforts to be integrated into urban planning, emphasizing the fulfillment of a sense of security not only physically but also psychologically. If the city fails to provide an adequate sense of security, it will lead to increased anxiety, discomfort, and ultimately limit community involvement in the use of public spaces. This study aims to identify design factors that influence women's sense of security and psychological safety in downtown areas. The research paradigm used is post-positivism with a quantitative approach, reinforced by walkthrough analysis techniques to produce more accurate findings. The results show that control factors are the most dominant aspect in influencing women's psychological security and safety, while sub-factors such as lighting, diversity of activities, availability of open spaces, and road conditions have also been shown to play a significant role in reducing women's anxiety when accessing public spaces. Thus, this study emphasizes the importance of city center design that is not only oriented towards physical function alone, but also pays attention to psychological aspects in order to create a safe, inclusive, and gender-friendly urban environment so that women can feel more protected and free to participate in urban life.